Do New Breeding Techniques in Ornamentals and Fruits Lead to Essentially Derived Varieties? - Krieger, Edgar; De Keyser, Ellen; De Riek, Jan (Frontiers in Plant Science, 2020)
Do New Breeding Techniques (NBT) lead to Essentially Derived Varieties (EDV)? It depends! It depends on the definition of EDV in the Plant Variety Right (PVR) laws and their interpretation by the courts. This paper aims at providing an overview of the EDV-concept and an analysis of the question, whether NBT lead to EDV, on the basis of the UPOV 1991 Act, the most recent UPOV Explanatory Notes on EDV of 2017 as well as some selected PVR laws. Almost 30 years ago the concept of EDV has been incorporated into the UPOV 1991 Act. In order to strengthen the rights of breeders, in particular to provide breeders of original genotypes an additional source of remuneration, a system of “Plant Variety Right specific dependency”, based on “essential derivation”, was developed. Only a very limited number of court cases have been concerned with EDV. However, an escalation in EDV-related conflicts can be expected in the future due to increased competition in the ornamental and fruit breeding business as well as to the application of more sophisticated NBT.